Rhetorical Moves in Introduction Sections of Applied Linguistic Research Articles of Different SINTA’s Ranking - Nova Pandan Sari; Azwandi Azwandi; Safnil Arsyad (Edu-Ling: Journal of English Education and Linguistics, 2022)
Rhetorical moves of RA (research article) introductions in various disciplines have been examined in many researchers, but few have investigated and compared one discipline in different national journal ranking. Therefore, this study is concerned to find out the similarities and differences of moves and steps in applied linguistic journal articles published in SINTA 1 to 6. A corpus of 30 RAs have been analyzed following Swales (2004) CARS model. Results were obtained through coding these 30 RAs by using observation checklist and mixed analysis. The finding revealed that all 3 moves such as establishing a territory, establishing a nichle, and presenting present work have appeared in all 30 RAs. Meanwhile the differences have found in the frequency of each step used, especially in move 2 and 3. In move 1, 100% of RAs have written step 1. Meanwhile in move 2, the frequency of step 2 was mostly used by authors in each journal of about 73%. Furthermore, there was only 1 step that not appeared in move 3 namely outlining research structure. Based on this finding, the writer should pay attention to various functions of each move and step in order to fulfil the aim of RA introductions.